Grassland to woodland transitions: Dynamic response of microbial community structure and carbon use patterns. Issue 6 (28th June 2016) - Creamer, Courtney A.; Filley, Timothy R.; Boutton, Thomas W.; Rowe, Helen I.
Abstract: Woodland encroachment into grasslands is a globally pervasive phenomenon attributed to land use change, fire suppression, and climate change. This vegetation shift impacts ecosystem services such as ground water allocation, carbon (C) and nutrient status of soils, aboveground and belowground biodiversity, and soil structure. We hypothesized that woodland encroachment would alter microbial community structure and function and would be related to patterns in soil C accumulation. To address this hypothesis, we measured the composition and δ 13 C values of soil microbial phospholipids (PLFAs) along successional chronosequences from C4 ‐dominated grasslands to C3 ‐dominated woodlands (small discrete clusters and larger groves) spanning up to 134 years. Woodland development increased microbial biomass, soil C and nitrogen (N) concentrations, and altered microbial community composition. The relative abundance of gram‐negative bacteria (cy19:0) increased linearly with stand age, consistent with decreases in soil pH and/or greater rhizosphere development and corresponding increases in C inputs. δ 13 C values of all PLFAs decreased with time following woody encroachment, indicating assimilation of woodland C sources. Among the microbial groups, fungi and actinobacteria in woodland soils selectively assimilated grassland C to a greater extent than its contribution to bulk soil. Between the two woodland types, microbes in the groves incorporated relatively more of the relict C4 ‐C than those in the clusters, potentially due to differences in below ground plant C allocation and organo‐mineral association. Changes in plant productivity and C accessibility (rather than C chemistry) dictated microbial C utilization in this system in response to shrub encroachment. Key Points: Microbial phospholipids examined along grassland to woodland chronosequence Increase in gram‐negative bacteria (cy19:0) with stand age Microbes predominately assimilate accessible woodland C